Application of the American Heart Association/American College of Cardiology/Heart Failure Society of America Heart Failure Staging Guidelines in Adults With Chronic Kidney Disease - Anna M. Zemke; Leila R. Zelnick; Joachim H. Ix; Alan S. Go; Edward D. Siew; Nisha Bansal (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background In 2022 the American Heart Association/American College of Cardiology/Heart Failure Society of America Guidelines for Management of Heart Failure proposed an updated staging system with cardiac biomarkers to diagnose heart failure (HF) and its severity. The applicability of this staging system in chronic kidney disease is not well established. Methods This is a prospective cohort study of 2415 participants from CRIC (Chronic Renal Insufficiency Cohort). Individuals were classified into HF stages using 2013 and 2022 American Heart Association/American College of Cardiology/Heart Failure Society of America HF guidelines using research echocardiograms, cardiac biomarkers (troponin T ≥10 ng/L [women], ≥15 ng/L [men], pro‐B‐type natriuretic peptide ≥125 pg/mL), laboratory measures, and history. Adjudicated outcomes of HF hospitalizations and all‐cause mortality are reported. Results In individuals with chronic kidney disease, participants with lower estimated glomerular filtration rates were more likely to be reclassified to a more advanced HF stage using the current proposed thresholds of hsTNT (high‐sensitivity troponin T) and NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide). The 2022 guidelines reclassified 55% of 2013 guideline stage A participants to stage B. HF hospitalization incidence rates differed when individuals were categorized into stage B HF based on elevated hsTNT or NT‐proBNP (1.7 per 100 person‐years) compared with echocardiographic abnormalities (2.9 per 100 person‐years), whereas death rates were similar between these groups. Conclusions Among individuals with CKD, the addition of elevated hsTNT or NT‐proBNP to HF staging reclassified nearly 20% of total participants into a higher HF stage. These individuals had similar mortality rates to those previously in higher stages, but they had lower HF hospitalization rates. Those with more advanced chronic kidney disease were more likely to be reclassified.